Is it the school or the farm? A story to tell... - María Mercedes Benavides Cárdenas (Corporación Universitaria Minuto de Dios, 2013)
This article presents, in a narrative way, a reflection that parts from a fieldwork conducted in the department of Arauca; is a story of a girl from the region, who is motivated to attend school in the village. The story offers some input to the discussion on some current problems affecting the Colombian rural school. Hence, from this little story, an analysis sets afloat that tackles the educational realities such as de-contextualization and subjugation of knowledge in rural schools. The text presents the need to create associations of epistemic dialogues in school taking into account the experiences and expertise of the people that have not been made visible in through the school media. In this style, themes like the milking songs (los cantos de ordeño) set afloat as an emergent pedagogy that shapes the social and cultural identity of the subject and the eastern community, Colombo-Venezuelan, of the eastern plains.